2007
DOI: 10.1007/s00262-007-0415-z
|View full text |Cite
|
Sign up to set email alerts
|

Langerhans cells and dendritic cells are cytotoxic towards HPV16 E6 and E7 expressing target cells

Abstract: Dendritic cells (DC) can be cytotoxic towards tumor cells by means of TNF family molecules expressed on the cell surface of activated DCs. Tumor cells expressing appropriate receptors are killed by DC, generating a source of antigen to be presented to the immune system. It has not been investigated whether Langerhans cells (LC) are selectively cytotoxic to tumor cells. This is of particular interest for epithelial tumor cells that physically interact with LC in vivo. Among epithelial tumors, the oncogenic proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 30 publications
1
11
0
Order By: Relevance
“…Sato et al showed that a single injection of TRAIL-transduced DCs could enhance the survival of leukemia-bearing mice [87]. Langerhans cells being the epithelial DCs, encounter epithelial tumor cells through IFN-induced TRAIL [88].…”
Section: Trailmentioning
confidence: 99%
“…Sato et al showed that a single injection of TRAIL-transduced DCs could enhance the survival of leukemia-bearing mice [87]. Langerhans cells being the epithelial DCs, encounter epithelial tumor cells through IFN-induced TRAIL [88].…”
Section: Trailmentioning
confidence: 99%
“…The other viral protein (E5) mediated acidification of endosomes affects antigen processing and presentation in APCs [218]. Both LCs and DCs have been shown to recognize and target tumor cells expressing HPV E6 and E7 for lysis [219]. …”
Section: Other Chronic Viruses and Dendritic Cellsmentioning
confidence: 99%
“…S100 immunoreactivity is characteristic of mature mDC that are effective in antigen presentation [9,[20][21][22][23][24]. Paraffin-embedded heart samples were sliced into 5 μm sections and then processed for antibody staining according to standard protocols to quantify mDC.…”
Section: Immunohistochemistrymentioning
confidence: 99%